Teologi Feminis Berdasarkan Kisah Para Rasul 9 : 36-42 - Tarumingi, Denny Adri (Educatio Christi, 2022)
A woman's work within the Church and Society is strongly felt by her real self-giving and dedication through community, family, local environment, work, Church ministry and social community.this is illustrated by the real role of Dorkas/Tabhita through Acts 9:36-42, because of her actions that have an impact on her surrounding life, especially her loving service that touches many people. This is because of the love of Jesus that touched her first, therefore a woman will be able to be a blessing and work wonderfully in the midst of limitations as a woman in the midst of the patriakhal system because of the love of Christ who lives in it. Likewise, the ministry of GMIM many women is truly a blessing to many, serving God earnestly because of the Love of Christ.